ABDOMINAL INCISIONS IN GENERAL SURGERY: A REVIEW (Association of Resident Doctors (ARD), University College Hospital, Ibadan, 2007)
There is this wrong notion that the only standard abdominal incision is the midline incision. Cases have been seen in which an abdominal incision extends from the xyphoid process to the symphysis pubis just to remove a perforated appendix! It is also not unusual to see a groin incision together with a lower abdominal incision for an obstructed inguinal hernia repair that “slipped” back into the abdominal cavity during preparation for surgery. Even though the trend nowadays in surgery is to opt for laparoscopic and mini-incision surgery, the basic rule in surgery is to have an incision that will be comfortable for the surgeon and provide adequate access to the area of pathology.